ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH PADA PT. BANK RAKYAT INDONESIA KANCA PONOROGO - Rafica, Vivia Maya (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
Company is a monetary service, thus it must win emulation which progressively more competitive. Bank Rakyat Indonesia cannot only rely on product development of eye service, but it must also force relation with all service users or clients who judge the make-up of the quality of service and product which on the market. This research aims to study and analyze the influences of The Quality of Service on the Costumer Satisfaction of PT. Bank Rakyat Indonesia (Persero) Kantor Cabang Ponorogo. The Quality of Service in this research uses three of the that is consist of: reliability, responsiveness and assurances have relationship with Costumer Satisfaction. If costumer feel satisfied, that make customer high probability to buys a service. In this research, Multiple regreression of technical analysis is applied. To test the impact, F test is applied and to test the partial influence, t test is applied at significant level 0,05. The number of samples used for this analysis are 266 consumers that comprise at Tabungan of PT. Bank Rakyat Indonesia (Persero) Kantor Cabang Ponorogo. The result of the research indicates that partially only reliability dimension which does not has an effect on the satisfaction of the client. The Quality of Service in this research uses three of the that is consist of: reliability, responsiveness and assurances have relationship with Costumer Satisfaction. If costumer feel satisfied, that make customer high probability to buys a service. In this research, Multiple regreression of technical analysis is applied. To test the impact, F test is applied and to test the partial influence, t test is applied at significant level 0,05. The number of samples used for this analysis are 266 consumers that comprise at Tabungan of PT. Bank Rakyat Indonesia (Persero) Kantor Cabang Ponorogo.